Purchasing Behavior Patterns Analysis and Knowledge of Multivitamin Consumer - Samarra, Ghaida Zahra; Rifin, Amzul; Suprehatin, Suprehatin (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The research aims to analyze behavioral patterns and experiences of purchasing multivitamins after the COVID-19 pandemic and analyze the level of consumer knowledge regarding multivitamins. The research results show that there has been a decrease in the consumption and purchase of multivitamins after the Covid-19 pandemic. However, respondents are still accustomed to taking multivitamins from the last year until now. Many respondents buy multivitamins through pharmacies and e-commerce. Sources of information about multivitamins are mostly obtained from professionals and friends/relatives. Instagram and TikTok are social media that are sources of information search. The availability of information and packaging labels was considered by respondents to be very important when purchasing multivitamins. Most respondents trust and are satisfied with the multivitamins they have purchased and intend to purchase again. The level of knowledge of respondents regarding multivitamins is good. It needs to be explained that multivitamins are not a type of medicine that can cure disease and cannot be consumed long-term.